A Simplified Neuronal Model for the Instigation and Propagation of Cortical Spreading Depression (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we construct a simplified neuronal model that is capableof simulating the instigation of cortical spreading depression (CSD) andpropagation of a CSD wave. Our model is a simplification and extension ofa single neuron model proposed in the literature for studying the instigationof CSD. Using the simplified neuronal model, we construct a network of thesesimplified neurons. This network model shows that the propagation of a CSDwave occurs naturally after it is instigated electrically or chemically.Although the model is simple, the speed of the CSD wave predicted by ourmodel is consistent with experimentally observed values. Finally, our modelallows us to investigate the effects of specific ion channels on the spreadof a CSD wave.